An uncommon cause of common presentation – Gall stone ileus: A case report and review of literature - Munghate, Anand; Mittal, Sushil; Singh, Harnam; Garg, Anjna; Singh, Gurpreet; Sharma, Jyoti (Asian Journal of Medical Sciences, 2014)
About 1%-4% of all cases of mechanical intestinal obstruction were caused by rare disease gallstone ileus. It is an uncommon complication of cholelithiasis. The formation of a fistula between the gallbladder and the duodenum may allow a gallstone to enter the intestinal tract. Gallstone ileus usually occurs in the elderly with a female predominance and is associated with a high mortality rate. The diagnosis of gallstone ileus entails a clinical challenge, especially in older patients in whom it may be easily overlooked. Here we report a case of 75 year old female patient presented in emergency with 4 day history of nausea, vomiting and pain in epigastric region. Emergent laparotomy was done and it was surprise to see that the cause of obstruction was gall stone ileus, enterolithotomy and repair was done. DOI: http://dx.doi.org/10.3126/ajms.v6i1.9307 Asian Journal of Medical Sciences Vol.6(1) 2015 112-114